Bioinspired microfibers for water collection. Issue 39 (26th September 2018) - Tian, Ye; Wang, Liqiu
Abstract : This review presents details of recent progress in bioinspired microfibers for water collection, including a systematic introduction to fiber types, fabrication methods, water-collecting mechanisms and behaviors. Abstract : Bioinspired microfibers for water collection have attracted increasing attention with the aim of alleviating water shortages in water-deficient areas. Here, we review recent progress in microfibers inspired by spider silk for water collection. We summarize and analyze the fiber types, fabrication methods, water-collecting mechanisms and water collection behaviors of bioinspired microfibers and make predictions about future trends in bioinspired microfibers for water collection. This review will be highly beneficial for the design of bioinspired microfibers and increasing their water collection efficiency, even in the fields of fiber-based sensors, oil-water separation, fluid control and smart functional materials.